Overcoming Adversity: Exploring Resiliency in the Lives of Youth Experiencing Homelessness - Manoni-Millar, Stéphanie (Université d'Ottawa / University of Ottawa, 2025)
Youth homelessness is a serious concern, and prolonged experiences of homelessness significantly impairs youths' participation in normative activities for their age group (e.g., schooling, social relationships, and work). They may jeopardize their ability to develop the skills needed for independence, autonomy, and transition to adulthood. This dissertation aims to advance the knowledge base of how resilience is developed among youth who experienced homelessness and investigate the role that resilience plays in their ability to achieve housing stability. Three studies were conducted to address the following research questions: [1] What factors hinder (risk) or support (protective) the development of resilient behaviours? And [2] What is the relationship between risk factors, protective resources, and housing stability? All three studies involved secondary data analysis from a multisite randomized controlled trial of Housing First for Youth (HF4Y) conducted in two Canadian cities. The first study responds to research question one and explores how risk and protective factors predict resilience over a two-year period. The study predictors of resilience at baseline, baseline predictors on resilience at a one-year follow-up and predictors at the one-year follow-up on resilience at a two-year follow-up. Predictors included risk factors: adverse childhood experiences, substance use, and mental health symptoms, and protective resources: social support, life skills, and psychological integration. While increased life skill predicted higher resilience at baseline, findings showed that a higher level of mental health symptoms significantly predicted lower resilience at baseline and at one year. Across time, an increased number of adverse childhood experiences and increased social support at one-year were significantly predictive of higher resilience at two years. Study 2 of this dissertation explored through qualitative interviews with 21 youth experiencing or who have experienced homelessness view protective resources and risk factors and how they displayed facets of resilience over one year. Stressors varied among participants, with childhood abuse and instability being the most prominent. Coping mechanisms included creating barriers to having unhealthy relationships, rebuilding healthy relationships, and reframing their circumstances. This study highlights the significance of community and relationship-based coping strategies alongside individual approaches, thus displaying the pivotal role of community support in fostering resilience among youth who have or are experiencing homelessness. Finally, Study 3 explores the relationship between risk factors, protective resources, and housing stability. The study was completed using a prospective design to see if there was change over time. Findings showed that risk factors did not significantly predict housing stability. However, social support was significantly related to and moderated the relationship between adverse childhood experiences and housing stability. In addition, the HF4Y Intervention significantly predicted housing stability in years one and two. The findings of the three studies highlight the importance of social and community support in developing resilience and achieving housing stability among youth who experience homelessness.
Keywords: Youth Homelessness; Resilience; Housing Stability; Coping